Development of Mobile-Based Learning Media Introduces Two-Dimentional Figure in Elementary Schools - Praciska, Mia Tri; Hikmawan, Rizki; Widodo, Suprih (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2024)
The use of mobile learning media can improve the quality of education by allowing students to access the learning process from home which can improve their understanding of the material. The purpose of the research is to develop mobile-based learning media introduces two-dimentional figure in elementary schools. This type of research uses R&D (Research and Development) with the ADDIE development model which includes Analyst, Design, Development, Implementation, and Evaluate. The results of the research show that mobile-based learning media introduces two-dimentional figure in elementary schools with the main features, namely material content, videos, textbooks, and student ability tests accompanied by discussion questions. The System Usability Scale (SUS) is used to evaluate the effectiveness of learning media. The research results show that the media has a high level of satisfaction, with an expert validation score of 88.33, a score of 74.09 in the one-to-one test, a score of 80.33 in small groups, a score of 99.47 in the field test. The application was also assessed as successful through black box testing. This study also found that mobile-based learning media on the introduction of two-dimentional figure can be used online or in the classroom, and the application is successful on various versions of Android.